INTESTINAL DISEASES IN PREGNANT WOMEN WITH COVID - 19 - Zamira R. Fayzullayeva,; Nasiba H. Kasimova ,; Gulomjon M. Turdibekov ,; Sevinch R. Kuchkarova , (Central Asian Journal of Medicine, 2024)
Purpose of the study. The purpose of our work is to study colon disease in pregnant women with Covid-19 and its effect on the embryo. Materials and methods. We studied 30 pregnant women of different ages with complaints of intestinal pain due to Covid-19 who were treated in the Department of Purulent Surgery of the Multidisciplinary Clinic of the Tashkent Medical Academy. Analysis and discussion of results. We used a survey method to identify the following majority - 50.9% of pregnant women had mild symptoms, 15.7% had moderate symptoms and 13.6% had severe symptoms. Conclusion. It was found that most pregnant women had a mild form of COVID-19. Pregnant women with COVID-19 have a higher incidence of preeclampsia, preterm birth, and cesarean section compared to pregnant women without COVID-19. Intrauterine vertical transmission of infection has not been identified. The frequency of complications in newborns corresponds to general population indicators.